2017
DOI: 10.1589/jpts.29.974
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of clinical features and quality of life after total knee replacement

Abstract: [Purpose] The purpose of this study is to provide fundamental information for efficient management of patients after a total knee replacement (TKR) through the evaluation of changes of range of motion, pain, functional level, and quality of life. [Subjects and Methods] For a total of 63 knee osteoarthritis patients, VAS, KSKS, KSFS, HSS, WOMAC scores and quality of life were evaluated for functional levels at pre-operation, post-operation, six months after operation, and 12 months after operation. [Results] Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 19 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…In most of the previous knee OA studies, the duration of follow up was long, and the reported improvement tended to be most obvious at 6 months after surgery [13]. Although the current study had a relatively short follow up, significant reductions in pain were observed, as reported previously in Wu, Tang, and Hong (2016).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In most of the previous knee OA studies, the duration of follow up was long, and the reported improvement tended to be most obvious at 6 months after surgery [13]. Although the current study had a relatively short follow up, significant reductions in pain were observed, as reported previously in Wu, Tang, and Hong (2016).…”
Section: Discussionsupporting
confidence: 74%
“…They concluded that the main causes of knee OA were overweight status (OR 1.98; 95% CI 1.57–2.20), obesity (OR 2.66; 95% CI 2.15–3.28), and female gender (OR 1.68; 95% CI 1.37–2.07) [12]. Several other longitudinal studies have focused on pain changes in knee OA patients before TKR and at varying time points after TKR [13]. For example, Lee et al, (2017) studied pain in 63 patients before and after TKR surgery, at 6 months and 12 months after they completed surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were carried out in Singapore [35,42,48] and two in Denmark [53,54]. One study was contributed by each of the following countries: Canada [56], Australia [31], Germany [39], Greece [40], South Korea [43], and Belgium [46]. The study area was not stated by one of the studies [49].…”
Section: Description Of Studies Included (Non-review Articles)mentioning
confidence: 99%
“…Out of twenty seven studies, four studies were assessed through Cochrane Risk of Bias Tool for randomized studies, three studies [52][53][54] reported to be of high quality whereas one [13] was found to be of moderate quality (Additional File 2). Among the non-randomized studies, thirteen studies [31,32,36,37,39,[41][42][43][44]47,48,51,55] were reported to be of moderate quality and six studies [33,34,38,45,46,49] were found to be of low quality. Only four studies [35,40,50,56]were reported to be of high quality.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%